"Strange animals": hybrid organisations in health care. Issue 7 (9th October 2017) - Powell, Martin; Castelli, Michele
Abstract : Purpose: The purpose of this paper is to critically explore hybrid organisations in health care. It examines the broad literature on hybrids focusing on issues of perspective, definition, sub-type and level. It then presents the results of the literature review of hybrid health care organisations, exploring which organisations have been viewed as hybrids, and then examining studies in more detail with respect to the research questions. Design/methodology/approach: It critically explores the literature on hybrid organisations in health care through a structured search. Findings: It is found that a wide variety of hybrid forms exist, but not clear what they combine or how they combine it. However, the level of depth from some of these studies is rather limited, with little consensus on definition, and relatively few drawing on any explicit conceptual perspective. It seems that the wider hybridity literatures have limited influence of studies of hybrid health care organisations. Originality/value: As far as the authors are aware, this paper is the first attempt to critically review the literature on hybrid organisations in health care. It is concluded that it is difficult to define and explain hybrid health care organisations. Health care hybrids appear to be chameleons as they appear to be able to change their form to different observers.